A review on path collisions and resources usage in hybrid optical Network on Chip (HONoC) - Razali R.A.; Othman M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Application specific integrated circuits; Bandwidth; Distributed computer systems; Fiber optic networks; Network architecture; Programmable logic controllers; Servers; System-on-chip; VLSI circuits; Distributed computations; High power consumption; Hybrid optical networks; Multi-core processor; path collisions; Resources optimization; routing; System-on-chip architecture; Network-on-chip